PROSPECTS FOR SHARIAH-COMPLIANT E-WALLET: ISSUES AND RECOMMENDATIONS - Abdul Muneem; Nor Fahimah Mohd Razif; Abdul Karim Ali; Faizah Hanim Zainuddin; Muhammad Izzul Syahmi Zulkepli (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Syariah and Law, Volume 13 Issue 1 Page (207-222)